Toward an implementation of recovery procedures for flexible manufacturing systems supervision - Berruet, P.; Toguyeni, A.K.A.; Elkhattabi, S.; Craye, E. (Computers in industry, 2000)
This paper first specifies Recovery and gives some trends about Recovery strategies. Then, it focuses on Reconfiguration. Several reactivity levels are defined according to the failure impact, flexibilities reserved during the exploitation phase, and flexibilities corresponding to the whole potentialities of the architecture. These enable to know if the FMS can react with its current configuration, or if its configuration has to be changed to go on with the production, or if the production has to be changed to maintain FMS availability. The Recovery procedures are implemented through a model named Operational Accessibility Graph, which has been emphasized by the definition of new attributes and methods. Some algorithms, based on the graph theory, are presented.